Group Reputations - An Experimental Foray - Steffen Huck; Gabriele K. Lünser (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2007)
Often information structures are such that while individual reputation building is impossible groups of agents would have the possibility of building up a reputation. We experimentally examine whether groups of sellers in markets that suffer from moral hazard are able to build up reputations and, thus, avoid market breakdown. We contrast our findings with situations where sellers alternatively can build up an individual reputation or where there are no possibilities for reputation building at all. Our results offer a rather optimistic outlook on group reputations. Even though each seller only receives some of the reputation benefits of withstanding short-run incentives, sellers are able to overcome the dilemma and successfully exploit the information structure.
Keywords: C72; C92; D40; L14; 330; Trust; group reputations; moral hazard; information conditions